Bank Concentration: An Analysis of Public Sector Banks in India - Dhawan, Shivam; Niharika (Gyan Management Journal, 2019)
Research  evidence  has  substantiated  that  consolidation  in  banking  sector  through  mergers  and  amalgamations  is  responsible  for  concentrated  banking  structure  in  India,  where  public  sector  commercial banks dictate the Indian banking sector in terms of its market share. In this context, the  present research study endeavors to assess the bank concentration byHerfindahl-Hirschman Index  (HHI) in terms of total assets for all the public sector commercial banks in India for a ten year time  period  from  2008  to  2017.The  research  study  also  aims  to  analyze  whether  or  not  the  bank  concentration has shown growth during the said time period. The results indicated that State Bank of  India has recorded the highest average market share in terms of total assets amongst all the public  sector banks in India followed by Bank of Baroda, whereas State Bank of Mysore has registered the  lowest average market share in terms of total assets. The trend analysis further revealed that even  though  the  overall  average  HHI  value  (0.090)  has  been  low  for  the  said  time  period,  butbank  concentration in terms of total assets has increased amongst all the public sector banks of India as  revealed by the positive growth percentage of HHI (20.22%) during the said time period.
Keywords: Bank Concentration; HHI; Public Sector Banks; Total Assets